2023
DOI: 10.1038/s41598-023-34726-3
|View full text |Cite
|
Sign up to set email alerts
|

A two-sample Mendelian randomization study of circulating lipids and deep venous thrombosis

Abstract: In view of the current debate about the relationship between lipids and deep venous thrombosis (DVT) in clinical studies, a two-sample Mendelian randomization (MR) study was conducted to clarify the effects of five circulating lipids (apolipoprotein A1, apolipoprotein B, low-density lipoprotein, high-density lipoprotein and triglycerides) on DVT from the perspective of genetic inheritance. Five lipids (exposure) were analysed by MR with DVT (outcome) from two different data sources. For the analysis, we used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The reliability of MR analysis was evaluated by sensitivity analysis, including heterogeneity tests, horizontal pleiotropy test and leave-one-out test (LOO). In the heterogeneity test, the Q- p -value greater than 0.05 indicated that there was no heterogeneity, and if there was heterogeneity, it was necessary to use the IVW test for random effects ( Luo et al, 2023 ). Horizontal pleiotropy test was used to assess the presence of confounders in the MR analysis, with a p -value of the result greater than 0.05 indicating that there was no horizontal pleiotropy effect ( Xu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The reliability of MR analysis was evaluated by sensitivity analysis, including heterogeneity tests, horizontal pleiotropy test and leave-one-out test (LOO). In the heterogeneity test, the Q- p -value greater than 0.05 indicated that there was no heterogeneity, and if there was heterogeneity, it was necessary to use the IVW test for random effects ( Luo et al, 2023 ). Horizontal pleiotropy test was used to assess the presence of confounders in the MR analysis, with a p -value of the result greater than 0.05 indicating that there was no horizontal pleiotropy effect ( Xu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%